A new perennial Erysimum species from Turkey, E. nemrutdaghense (Brassicaceae) - Mutlu Bi̇rol (Phytotaxa, 2018)
In this study, Erysimum nemrutdaghense Mutlu (Brassicaceae) is described as a new species from the province of Adıyaman in the South-east Anatolia. In order to determine the phylogenetic relationships of the new species, a portion of the nuclear ribosomal DNA sequences of ITS region was used. In addition to the new species, ITS regions of five Erysimum species were sequenced. Erysimum sintenisianum Bornm., E. lazistanicum (Rupr.) Lipsky, and E. stenophyllum Polatschek were sequenced in this study for the first time. The diagnostic morphological and phylogenetic characteristics are discussed with similar species. SEM images of trichomes on different parts of siliqua, stigma, and seed are given. Chromosome number of the new species is found to be 2n=16.